A survey report on the donkey original breeding farms in China: Current aspects and future prospective - Zhang, Zhenwei; Huang, Bingjian; Wang, Yonghui; Zhu, Mingxia; Liu, Guiqin; Wang, Changfa (Frontiers in Veterinary Science, 2023)
The number of the large-scale donkey breeding farms in China has increased dramatically. However, information regarding the situation of a Chinese donkey population under large-scale donkey breeding farms is limited. This survey report was conducted using questionnaires online to investigate the current situation of the donkey original breeding farms in China, in terms of donkey stock, local breeds, reproductive parameters, growth and lactation performance, and future perspectives. China has developed the donkey reserve system based on national, provincial and nongovernmental (self-own) donkey original breeding farms. In the present study, a total of 38 donkey original breeding farms concentrated in Northen of China were studied, and 52% of them keep their donkeys with a stocking density of 100~500 donkeys. China is rich in various local donkey breeds, and 16 local donkey breeds including large-sized, medium-sized and small-sized breeds were collected in our survey. Dezhou donkey are prevalent with a percentage of more than 57% of the total donkeys, while the Cullen donkeys belong to small-sized donkey breeds are scare. The reproductive efficiency and donkey productivity were different across donkey farms, indicating potential differences in management and breeding practices between different donkey original breeding farms. The artificial insemination has been performed in these donkey farms with an average proportion of 73%. Regarding the donkey productivity, the national and provincial donkey original breeding farms showed a higher birthweight and fat content in donkey milk than self-own farms. Furthermore, our results indicate that the donkey breeds with different body size also have important influence on the reproduction parameters and donkey productivity, with the large-sized donkeys had better performance compared to the small-sized donkeys. In summary, our survey provided valuable baseline information on the situation of donkey population dynamics in the donkey original breeding farms. However, further study is required in the future to investigate the factors such as donkey health care, management and nutrition during breeding, fattening and lactation that influence donkey productivity under large-scale farm systems.